A Fruit Fly, Anastrepha nigrifascia Stone (Insecta: Diptera: Tephritidae) - Howard V. Weems (EDIS)
This small yellowish fruit fly, somewhat larger than a house fly, with rather long, patterned wings is limited to the Florida Keys, from Key Largo Key to Key West. Its two known hosts are sapodilla and wild-sapodilla. This revised 2-page fact sheet was written by H. V. Weems, Jr., and published by the UF Department of Entomology and Nematology, March 2012.